The role of placental growth factor as a biomarker in patients with resectable gastric cancer - Rompen, Ingmar F.; Nerz, Daniel; Crnovrsanin, Nerma; Hu, Wenjun; Zimmer, Sarah; Musa, Julian; Haag, Georg Martin; Fiedler, Timon; Longerich, Thomas; Saeedi, Mohammed al; Peters, Leila; Schmidt, Thomas; et al. (Journal of gastrointestinal surgery, 2025)
Background - Systemic treatment failure and an insufficient treatment response to neoadjuvant treatment underscore the urgency for better tumor-directed treatment for patients with resectable gastric cancer. The angiogenic pathway has repeatedly shown predictive and prognostic value in this cancer subtype; however, the relevance of placental growth factor (PlGF) is unclear. Therefore, we aimed to assess PlGF as a prognostic and predictive biomarker. - Methods - This translational study was performed in 2 phases. First, adenogastric (AGS) and Mie-Kinen-45 (MKN-45) gastric cancer cell lines were treated with recombinant angiogenic growth factors and chemotherapeutic agents. Cell count analyses and quantitative polymerase chain reaction were performed to assess proliferative and cytotoxic effects. Second, prospectively collected blood samples of patients undergoing surgical treatment for gastric cancer were assessed by enzyme-linked immunosorbent assay and correlated to clinicopathologic outcomes. - Results - In MKN-45 cells, treatment with PlGF led to increased cell numbers after 72 h (P <.01), whereas proliferative effects of PlGF were less pronounced in the AGS cell line. Addition of PlGF lowered the cytotoxic effect of standard chemotherapeutic agents as evidenced by significant differences in cell growth at low concentrations of cisplatin (5 µM cisplatin vs 5 µM cisplatin plus PlGF) and high concentrations of paclitaxel (25 µM paclitaxel vs 25 µM paclitaxel plus PlGF) in both AGS and MKN-45 cell cultures after 72 h (all comparisons P <.05). In patients with gastric cancer (n = 68), high PlGF concentrations were significantly associated with more recurrences (estimated 5-year-recurrence rate, 34% [high PlGF] vs 6% [low PlGF]; log-rank P =.009) but no association was found with pathologic treatment response, tumor size, nodal stage, or tumor grade. - Conclusion - The association of elevated PlGF expression with disease-specific survival despite no correlation with other tumor-specific prognostic factors may indicate that PlGF could be used as an independent prognostic biomarker in gastric cancer. The ability to predict resistance to neoadjuvant treatment, as demonstrated in cell experiments, requires further investigation in a clinical setting.
Online verfügbar: 3. April 2025, Artikelversion: 16. April 2025
Gesehen am 11.11.2025